Method for efficiently removing VOCs (Volatile Organic Compounds) through plasma in-situ coupling ferroelectric catalyst
By preparing a porous catalyst with ferroelectric properties and coupling it with plasma, the problem of low efficiency of plasma catalysts in the prior art when dealing with low concentrations of difficult to degrade VOCs is solved, and an efficient and environmentally friendly VOCs removal effect is achieved.
Patent Information
- Application Number
- CN202411912870.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-11
AI Technical Summary
When existing plasma catalytic technology deals with VOCs difficult to degrade at low concentrations, there are problems such as low energy density in the discharge reaction zone, low coupling efficiency between plasma and catalyst, and poor pollutant degradation effect.
By preparing a porous catalyst with ferroelectric properties, its specific surface area and active site are increased, and placed in the plasma region, the efficient removal of VOCs is achieved by using the efficient coupling between the plasma and the catalyst.
The coupling efficiency of plasma catalysts is significantly improved, the removal efficiency of difficult-to-degrade VOCs is improved, and the purification effect is improved, making the plasma catalytic process more green, environmentally friendly and efficient.
Smart Images

Figure BDA0005207054230000051 
Figure BDA0005207054230000052 
Figure BDA0005207054230000091
Abstract
Description
Technical Field
[0001] The present application relates to a method for efficiently removing VOCs by in-situ plasma coupling with a ferroelectric catalyst, and belongs to the field of plasma catalysis technology and gas pollutant purification technology. Background Art
[0002] The emission of volatile organic compounds (VOCs) has brought severe challenges to the atmospheric environment. Common VOCs include hydrocarbons, aromatics, ketones, esters, alcohols, ethers, aldehydes, amines, nitriles, etc. These pollutants are not only toxic, but some are also carcinogenic. In particular, the highly stable and difficult to degrade VOCs have a long environmental half-life, low concentration, and persist in the air, water, and soil, causing greater harm to human health and the ecosystem. In the prevention and control of air pollution, the efficient removal of difficult to degrade VOCs waste gas has always been a key and difficult issue.
[0003] Plasma catalytic technology has attracted widespread attention in the process of VOCs treatment due to its advantages such as wide application range, fast reaction rate and mild operating conditions. However, this technology still generally has problems such as low energy density in the discharge reaction zone and poor pollutant degradation effect in the purification and treatment process of low-concentration difficult-to-degrade VOCs. For example, patent document CN 111921524A discloses an ABO3-type perovskite catalyst, a preparation method and its application in plasma-coordinated catalysis of VOCs. The overall process of the invention technology is simple, which overcomes the disadvantages of using a single plasma or catalytic technology alone. However, due to the limitations of the perovskite catalyst used (the high synthesis temperature leads to a small specific surface area of the catalyst and the discharge plasma mode cannot be changed), the coupling efficiency of the plasma and the catalyst in the plasma catalytic system constructed by the invention is not high, the working efficiency is low, and the removal rate of difficult-to-degrade VOCs is more difficult. This greatly reduces the possibility of the actual application of plasma catalytic technology in the removal of difficult-to-degrade VOCs, and also limits the large-scale promotion and application of this technology in the field of waste gas purification. Summary of the invention
[0004] In view of the shortcomings of the prior art, this application proposes a technical solution to significantly improve the coupling efficiency between plasma and catalyst and thus improve the performance of plasma catalysis technology for VOCs removal. By synergistically controlling the properties and structure of the catalyst, the interaction between plasma and catalyst can be regulated, thereby enhancing the plasma catalysis in the system. The specific implementation method is: preparing and synthesizing a catalyst with ferroelectric properties to enhance the catalyst's response to the discharge electric field, preparing a porous structure by a template method to increase the specific surface area and active sites of the ferroelectric catalyst, and then placing the designed and synthesized catalyst in the plasma zone, and removing difficult-to-degrade VOCs with the help of the efficient coupling between plasma and catalyst, solving the problems of low energy density in the discharge reaction zone, low plasma and catalyst coupling efficiency, and poor pollutant degradation effect, making the plasma catalysis process more green, environmentally friendly and efficient in the waste gas treatment process.
[0005] This application adopts the following technical solutions:
[0006] According to the first aspect of the present application, a method for efficiently removing VOCs by in-situ plasma coupling with a ferroelectric catalyst is provided, comprising the following steps:
[0007] Introducing VOCs gas into the plasma region so that the VOCs gas contacts the ferroelectric catalyst placed in the plasma region;
[0008] The plasma zone is provided by a plasma generator through a dielectric barrier discharge method, and the power supply of the plasma generator is a pulse power supply or an AC power supply;
[0009] The ferroelectric catalyst comprises a porous metal oxide having ferroelectric properties;
[0010] The porous metal oxide is a perovskite material with a chemical composition of ABO3, wherein:
[0011] A is selected from one of Ba, Li, La, Ca and Sr;
[0012] B is selected from one of Ti, Nb, Fe, Co and Cu.
[0013] Optionally, within the plasma region, the catalyst is coupled to the plasma discharge in situ.
[0014] Optionally, the ferroelectric catalyst is prepared by a method comprising the following steps:
[0015] S1, slowly adding source A solution to source B solution, stirring, to obtain a metal salt precursor solution;
[0016] Wherein, the A source solution is an aqueous solution of the A metal salt, and the B source solution is an alcohol solution containing the B metal alkoxide;
[0017] S2, placing the template in a metal salt precursor solution, allowing it to stand for aging to form a gel, and then centrifuging and drying to obtain a template impregnated with the metal salt precursor;
[0018] S3, heat-treating the template impregnated with the metal salt precursor to remove the template agent to obtain a solid metal oxide phase;
[0019] The heat treatment is carried out in an oxidizing atmosphere;
[0020] S4. In an oxidizing atmosphere, calcining the solid metal oxide phase to obtain the ferroelectric catalyst.
[0021] Optionally, the ferroelectric catalyst further comprises a noble metal element supported on the surface of the porous metal oxide;
[0022] The noble metal is selected from at least one of Au, Pt, Ag, and Pd;
[0023] In step S1, the B source solution also includes a soluble precious metal salt;
[0024] In the step S3, the heat treatment is performed in a reducing atmosphere.
[0025] Optionally, in step S1, the mass concentration of metal salt A in the aqueous solution of metal salt A is 1 to 5%;
[0026] Optionally, in step S1, in the alcohol solution of metal alkoxide B, the volume concentration of metal alkoxide B is 10-50%;
[0027] Optionally, in step S1, the usage ratio of metal salt A to metal alkoxide B is 1 g: 1-5 mL.
[0028] Optionally, in step S2, the usage ratio of the metal salt precursor solution to the template agent is 1 mL: 0.1-1 g.
[0029] Optionally, in step S1 and step S2, the template is selected from a PMMA template prepared by the Stober-Frink method.
[0030] PMMA has a rich pore structure, including micropores, mesopores, macropores or a combination of the three.
[0031] Optionally, in step S2, the conditions for static aging include: the aging time is 12 to 48 hours.
[0032] Optionally, in step S2, the number of centrifugation is 2 to 3 times, and the drying is continuous drying at 50 to 120° C. for 8 to 16 hours.
[0033] Optionally, in step S3, the heat treatment conditions include: a heat treatment temperature of 400 to 800° C. and a heat treatment time of 8 to 16 hours.
[0034] Optionally, in step S5, the calcination conditions include: a calcination temperature of 300 to 500° C. and a calcination time of 1 to 9 hours.
[0035] Optionally, in step S5, the calcination conditions include: heating to 300-350°C and maintaining for 0.5-3h, then heating to 450-500°C and maintaining for 0.5-6h.
[0036] Optionally, the working conditions of the pulse power supply are: pulse time is 2 to 10 ns, pulse frequency is 1 to 10 kHz;
[0037] The working conditions of the AC power supply are: frequency of 50kHz to 100kHz and discharge power of 10 to 200W.
[0038] Optionally, the flow rate of the VOCs gas is 100 to 5000 mL / min;
[0039] The concentration of VOCs gas is 20-3000ppm.
[0040] Optionally, the VOCs gas contains any one or more of highly stable, difficult-to-degrade aromatics, esters, alcohols, ethers, aldehydes, amines or nitriles.
[0041] The beneficial effects of this application include:
[0042] (1) The present application adopts an in-situ coupling method between plasma and catalyst, which is beneficial to the short-lived active species generated by the catalyst in the plasma and significantly improves the coupling efficiency between the two.
[0043] (2) The present application prepares a porous catalyst with ferroelectric properties, which greatly increases the specific surface area of the ferroelectric catalyst and is also conducive to the generation of uniform plasma in the catalyst pores, thereby enhancing the interaction between the plasma and the catalyst surface.
[0044] (3) The present application selects to use a catalyst with ferroelectric properties, whose ferroelectricity can enhance the discharge intensity under the same conditions by responding to the electric field, so that the isotropically coupled catalyst region produces a more efficient discharge, significantly improving the removal efficiency of difficult-to-degrade VOCs.
[0045] (4) The present application combines dielectric barrier discharge plasma technology with a ferroelectric catalyst for catalytic degradation of VOCs. The entire treatment process can be started and stopped quickly, has high energy efficiency, and has better treatment effects. The uniform and mild characteristics of the plasma can significantly control the generation of secondary pollutants, making the treatment process more environmentally friendly and efficient. DETAILED DESCRIPTION
[0046] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0047] In the embodiment of the present application, the PMMA template is prepared by the Stober-Frink method, and the specific steps are as follows:
[0048] a. Take a 2000ml three-necked flask, install a condenser at the top of the three-necked flask, and two ports on the left and right sides, one of which is for inert gas, and the other is plugged for adding reactants later. Add 850ml of deionized water to the three-necked flask, pass inert gas, and stir steadily in a water bath at 80℃ for 30min;
[0049] b. Take two 50ml beakers, add 1.8g KPS initiator and 30ml deionized water to one beaker, stir at 80℃ for 20min; add 20ml deionized water to the other beaker, stir at 80℃ for 20min;
[0050] c. Take 100 ml of MMA (methyl methacrylate) monomer and add it into a 2000 ml three-necked flask through the port with a stopper, then add the KPS solution stabilized at 80°C into the three-necked flask through the same port, and wash the KPS beaker with 20 ml of deionized water in another beaker and add it into the three-necked flask. After reacting at 80°C for 30 minutes, pour it into a large beaker filled with 1000 ml of deionized water and mix to obtain a PMMA microsphere emulsion;
[0051] d. Centrifuge the PMMA microsphere emulsion at 6000 rpm for about 90 minutes, precipitate the supernatant with a pipette, transfer the remaining white sample in the centrifuge tube to a beaker, weigh its mass, and then add deionized water to prepare an emulsion with about 20 wt% PMMA. Disperse the emulsion by ultrasonic for 60-90 minutes until the emulsion is uniform, and obtain a PMMA self-assembly template emulsion;
[0052] e. Take an appropriate amount of PMMA self-assembly template emulsion into a flat-bottom container and evaporate the water in a 60°C water bath to promote the self-assembly of PMMA microspheres. After the water is completely evaporated, the self-made PMMA template agent is obtained.
[0053] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0054] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0055] The calculation method of the removal rate (conversion rate) of toluene in this application is:
[0056]
[0057] n0=C0×C v
[0058] n t =C t ×V t (V t =V0)
[0059] In the formula, C0, C t are the gas phase toluene concentrations at the initial and degradation time t (mg·m -3 ), the degradation time of this patent is 60min;
[0060] n0、n t are the amount of toluene in the gas phase at the initial and degradation time t (mol), respectively;
[0061] η is the toluene conversion rate;
[0062] V0, V t are the volumes of gaseous toluene at the initial and photodegradation time t (m 3 ).
[0063] The calculation method of the energy efficiency of the plasma region in this application is:
[0064]
[0065] Where P dis , P in are the discharge power and input power during plasma discharge respectively.
[0066] According to one embodiment of the present application, a method for efficiently removing VOCs by in-situ plasma coupling with ferroelectric catalysts includes the following steps: preparing a catalyst by a template method, specifically preparing a solution of metal oxide and precious metal precursors (metal salts), impregnating the template with the configured metal salt solution, solidifying the sample after aging, centrifugation, and drying, then subjecting the sample to heat treatment to remove the template and to phase the metal oxide, and then subjecting the catalyst to thermal reduction treatment to obtain a catalyst having a high specific surface area, porosity, and ferroelectric properties, placing the obtained catalyst in-situ in the plasma zone for efficient coupling, and thereby synergistically catalyzing the removal of difficult-to-degrade VOCs.
[0067] Example 1
[0068] The target catalyst (porous BaTiO3) was prepared by following the steps below:
[0069] a. Weigh 10 mL of tetrabutyl titanate and add it dropwise to 50 mL of anhydrous ethanol while stirring magnetically to form a uniform titanium source solution; weigh 2.61 g of barium nitrate and dissolve it in 100 mL of water to form a barium source solution. Slowly add the titanium source solution dropwise to the barium source solution while stirring continuously to form a uniform and stable metal salt precursor solution.
[0070] b. Weigh 10 ml of the metal salt precursor solution obtained in step a, and place 1 g of PMMA template in the precursor solution and age it at room temperature for 12 hours to form a gel.
[0071] c. The gel in step b was centrifuged at 20,000 r / min for 3 times, each time for 1 hour, and then the excess precursor was filtered off and dried at 50° C. for 12 hours to obtain a solid sample.
[0072] d. Weigh 0.5 g of the dried solid sample and put it into a tubular furnace for calcination. First, heat it to 400°C in a nitrogen atmosphere and keep it for 2.5 hours to remove the PMMA template. Then cool it to room temperature. Then, heat it to 300°C in an air atmosphere and keep it for 1.5 hours, then heat it to 500°C and continue treating it at 500°C for 4 hours to finally obtain the target catalyst (porous BaTiO3).
[0073] Comparative Example 1 Conventionally synthesized ferroelectric catalyst
[0074] The conventionally synthesized control catalyst (BaTiO3) was prepared in the following steps:
[0075] a. Weigh 10 mL of tetrabutyl titanate and add it dropwise to 50 mL of anhydrous ethanol while stirring magnetically to form a uniform titanium source solution; weigh 2.61 g of barium nitrate and dissolve it in 100 mL of water to form a barium source solution. Slowly add the titanium source solution dropwise to the barium source solution while stirring continuously to form a uniform and stable metal salt precursor solution.
[0076] b. Weigh 10 ml of the metal salt precursor solution obtained in step a and age it at room temperature for 12 hours until it turns into a gel state.
[0077] c. Place the gel in step b in an oven and dry it at 100° C. for 12 hours to remove the solvent and moisture in the gel, and finally obtain a dry gel.
[0078] d. Place the dry gel in step c into a muffle furnace, heat it to a predetermined temperature of 1000° C. at a certain heating rate of 10° C. / min, calcine for 3 hours, grind it, and obtain a control catalyst (BaTiO 3 ).
[0079] Comparative Example 2
[0080] The control catalyst (porous LaCoO3) was prepared by following the steps below:
[0081] A. Take 4.33 g La(NO3)3·6H2O and 2.91 g Co(NO3)2·6H2O, dissolve them in 100 mL deionized water and stir evenly to obtain a metal salt precursor solution;
[0082] b. Weigh 10 ml of the metal salt precursor solution obtained in step a, and place 1 g of PMMA template in the precursor solution and age it at room temperature for 12 hours to form a gel.
[0083] c. The gel in step b was centrifuged at 20,000 r / min for 3 times, each time for 1 hour, and then the excess precursor was filtered off and dried at 50° C. for 12 hours to obtain a solid sample.
[0084] d. Weigh 0.5 g of the dried sample and put it into a tubular furnace for calcination. First, heat it to 400°C in a nitrogen atmosphere and keep it for 2.5 hours to remove the PMMA template. Then cool it to room temperature. Then, heat it to 300°C in an air atmosphere and keep it for 1.5 hours. Then heat it to 500°C and continue treating it at 500°C for 4 hours to obtain a control catalyst (porous LaCoO3).
[0085] Test Example 1
[0086] (I) Effect of conventionally synthesized ferroelectric catalysts on plasma catalytic removal of toluene
[0087] The experimental process is as follows: 1000ppm toluene is introduced, the total gas flow rate is 1000ml / min, dielectric barrier discharge is adopted, the input power is within the range of 20W at room temperature and pressure, 0.2g of the control catalyst (BaTiO3) in comparative example 1 is taken and placed in the plasma discharge zone to investigate its synergistic catalytic effect on toluene with plasma. The results are shown in Table 1. The removal rate of toluene by the conventionally synthesized BaTiO3 catalyst is only 64.2%, and the energy efficiency of the plasma zone is 43.1%.
[0088] (II) Effect of target catalyst on plasma catalytic removal of toluene
[0089] The experimental process is as follows: 1000ppm toluene is introduced, the total gas flow rate is 1000ml / min, dielectric barrier discharge is adopted, the input power is within the range of 20W at room temperature and pressure, 0.2g of the target catalyst (porous BaTiO3) with ferroelectricity synthesized in Example 1 is taken and placed in the plasma discharge zone, and its catalytic effect on toluene in synergy with plasma is investigated. The results are shown in Table 1. The target catalyst (porous BaTiO3) is used for plasma catalytic removal of toluene with a maximum efficiency of 94.1%, which is significantly higher than the control catalyst (BaTiO3) with a non-porous structure. In addition, the energy efficiency of the plasma zone is increased to 49.4%, and the energy density is excellent compared with other systems.
[0090] (III) Effect of target catalyst on traditional thermal catalytic removal of toluene
[0091] The experimental process is as follows: 1000 ppm toluene is introduced, the total gas flow rate is 1 000 ml / min, 0.2 g of the target catalyst (porous BaTiO3) with ferroelectricity synthesized in Example 1 is taken, and its thermal catalytic toluene oxidation effect at 300°C is investigated. The results are shown in Table 1. The traditional thermal catalytic effect of the target catalyst is not high, and the toluene conversion rate does not reach 70%.
[0092] (IV) Effect of other catalysts on plasma catalytic removal of toluene
[0093] The experimental process is as follows: 1000ppm toluene is introduced, the total gas flow rate is 1000ml / min, dielectric barrier discharge is used, the input power is within the range of 20W at room temperature and pressure, 0.2g of the typical non-ferroelectric control catalyst (porous LaCoO3) synthesized in Comparative Example 2 is taken and placed in the plasma discharge zone, and its catalytic effect on toluene in coordination with plasma is investigated. LaCoO3 catalyst is a classic perovskite catalyst, which often shows good results in the oxidation removal of toluene. It can be seen from Table 1 that its plasma catalytic removal efficiency of toluene exceeds 80%, but it is still not as good as the catalytic efficiency of the target catalyst prepared by this method.
[0094] (V) Effect of the target catalyst mixed with other catalysts for plasma catalytic removal of toluene
[0095] The experimental process is as follows: 1000ppm toluene is introduced, the total gas flow rate is 1000ml / min, dielectric barrier discharge is used, the input power is within the range of 20W at room temperature and pressure, 0.1g of the target catalyst (porous BaTiO3) with ferroelectricity synthesized in Example 1 is mixed with 0.1g of the typical non-ferroelectric control catalyst (porous LaCoO3) synthesized in Comparative Example 2, and placed in the plasma discharge zone to investigate its catalytic effect on toluene in coordination with plasma. As can be seen from the results in Table 1, the removal efficiency of the mixed system for toluene reaches 87.4%. Although the removal effect is improved compared with the LaCoO3 catalyst, it is still lower than the porous BaTiO3 catalyst, and the energy efficiency of the plasma zone is also reduced. In the plasma catalysis experiment, the ferroelectric material is mixed with a catalyst with higher activity. The purpose is to enhance the discharge with the help of the properties of the ferroelectric material, while allowing the catalyst to exhibit excellent catalytic activity.
[0096] Table 1 Effect of porous BaTiO3 and different systems on removal of toluene
[0097]
[0098] Example 2
[0099] The target catalyst (porous LiNbO3) of other metal elements is prepared according to the following steps:
[0100] a. Weigh 10 mL of tetrabutyl niobate and add it dropwise to 50 mL of anhydrous ethanol while stirring magnetically to form a uniform niobium source solution; weigh 4.23 g of lithium chloride and dissolve it in 100 mL of deionized water to form a lithium source solution. Slowly add the niobium source solution dropwise to the lithium source solution while stirring continuously to form a uniform and stable metal salt precursor solution.
[0101] b. Weigh 10 ml of the metal salt precursor solution obtained in step a, and place 1 g of PMMA template in the precursor solution and age it at room temperature for 12 hours to form a gel.
[0102] c. The gel in step b was centrifuged at 20,000 r / min for 3 times, each time for 1 hour, and then the excess precursor was filtered off and dried at 50° C. for 12 hours to obtain a solid sample.
[0103] d. Weigh 0.5 g of the dried sample and put it into a tubular furnace for calcination. First, heat it to 400°C in a nitrogen atmosphere and keep it for 2.5 hours to remove the PMMA template, then cool it to room temperature, then heat it to 300°C in an air atmosphere and keep it for 1.5 hours, then heat it to 500°C and continue treating it at 500°C for 4 hours to finally obtain the target catalyst (porous LiNbO3).
[0104] Comparative Example 3
[0105] The control catalyst (LiNbO3) was prepared by following the steps below:
[0106] a. Weigh 10 mL of tetrabutyl niobate and add it dropwise to 50 mL of anhydrous ethanol, stirring magnetically at the same time to form a uniform niobium source solution; weigh 4.23 g of lithium chloride and dissolve it in 100 mL of water to form a lithium source solution. Slowly add the niobium source solution dropwise to the lithium source solution, stirring continuously during the addition, to form a uniform and stable metal salt precursor solution.
[0107] b. Weigh 10 ml of the metal salt precursor solution obtained in step a and age it at room temperature for 12 hours until it turns into a gel state.
[0108] c. Place the gel in step b in an oven and dry it at 100° C. for 12 hours to remove the solvent and moisture in the gel, and finally obtain a dry gel.
[0109] d. Place the dry gel in step c into a muffle furnace, heat it to a predetermined temperature of 1000° C. at a certain heating rate of 10° C. / min, calcine for 3 hours, grind it, and obtain a control catalyst (LiNbO 3 ).
[0110] Test Example 2
[0111] (I) Effect of conventionally synthesized ferroelectric catalysts on plasma catalytic removal of toluene
[0112] The experimental process is as follows: 1000ppm toluene is introduced, the total gas flow rate is 1000ml / min, dielectric barrier discharge is adopted, the input power is within the range of 20W at room temperature and pressure, 0.2g of the conventionally synthesized control catalyst (LiNbO3) in Comparative Example 3 is taken and placed in the plasma discharge zone, and its synergistic catalytic effect on toluene with plasma is investigated. The results are shown in Table 2. The removal rate of toluene by the conventionally synthesized LiNbO3 catalyst is 62.5%, and the energy efficiency is 42.2%.
[0113] (II) Effect of target catalyst on plasma catalytic removal of toluene
[0114] The experimental process is as follows: 1000ppm toluene is introduced, the total gas flow rate is 1000ml / min, dielectric barrier discharge is used, the input power is within the range of 20W at room temperature and pressure, 0.2g of the target catalyst (porous LiNbO3) with ferroelectricity synthesized in Example 2 is taken and placed in the plasma discharge zone, and its catalytic effect on toluene in synergy with plasma is investigated. The results are shown in Table 2. The target catalyst is used for plasma catalytic removal of toluene up to 93.5%, and the energy efficiency of the plasma zone also reaches 48.4%. The removal efficiency and energy efficiency are still significantly higher than those of LiNbO3 with a non-porous structure, which proves that the advantages of the target catalyst prepared by this synthesis method are universal.
[0115] (III) Effect of target catalyst on traditional thermal catalytic removal of toluene
[0116] The experimental process is as follows: 1000 ppm toluene is introduced, the total gas flow rate is 1 000 ml / min, 0.2 g of the target catalyst (porous LiNbO3) with ferroelectricity synthesized in Example 2 is taken, and its thermal catalytic toluene oxidation effect at 300°C is investigated. The results are shown in Table 2. The traditional thermal catalytic effect of the target catalyst is also not high, and the toluene conversion rate fails to reach 70%.
[0117] (IV) Effect of plasma catalytic removal of toluene after the target catalyst is mixed with other catalysts
[0118] In plasma catalysis experiments, people usually mix ferroelectric materials with highly active catalysts, with the purpose of enhancing discharge with the help of the properties of ferroelectric materials and allowing the catalyst to exhibit excellent catalytic activity. Therefore, the experimental process is as follows: 1000ppm toluene is introduced, the total gas flow rate is 1000ml / min, dielectric barrier discharge is used, the input power is within the range of 20W at room temperature and pressure, 0.1g of the target catalyst (porous LiNbO3) with ferroelectricity synthesized in Example 2 is mixed with 0.1g of the typical non-ferroelectric control catalyst (porous LaCoO3) synthesized in Comparative Example 2, and placed in the plasma discharge zone, and its catalytic effect on toluene in coordination with plasma is investigated. As can be seen from the results in Table 2, the removal efficiency of the mixed system for toluene reaches 87.2%, and the energy efficiency also reaches 45.1%, but the removal efficiency and energy are still lower than those of the porous structure LiNbO3 catalyst, which once again confirms the advantages of the preparation method of this patent.
[0119] Table 2 Effect of different porous LiNbO3 systems on removal of toluene
[0120]
[0121] Example 3
[0122] The target catalyst (porous Pt@BaTiO3) was prepared according to the following steps:
[0123] a. Weigh 10 mL of tetrabutyl titanate and add it dropwise into 40 mL of anhydrous ethanol while stirring magnetically to form a uniform titanium source solution; weigh 2.61 g of barium nitrate and dissolve it in 50 mL of deionized water to form a titanium source solution; weigh 3.19 g of Pt(NO3)2 and dissolve it in 500 mL of deionized water, first mix the titanium source solution with the precious metal solution, and then slowly add the mixed solution dropwise into the barium source solution, stirring continuously during the addition, to form a uniform and stable metal salt precursor solution.
[0124] b. Weigh 10 ml of the metal salt precursor solution obtained in step a, and place 1 g of PMMA template in the precursor solution and age it at room temperature for 12 hours to form a gel.
[0125] c. The gel in step b was centrifuged at 20,000 r / min for 3 times, each time for 1 hour, and then the excess precursor was filtered off and dried at 50° C. for 12 hours to obtain a solid sample.
[0126] d. Weigh 0.5 g of the dried sample and put it into a tubular furnace for calcination. First, heat it to 400°C in a hydrogen atmosphere and keep it for 2.5 hours to remove the PMMA template and reduce the precious metal precursor to a metallic state. Then cool it to room temperature and then heat it to 300°C in an air atmosphere and keep it for 1.5 hours. Then heat it to 500°C and continue treating it at 500°C for 4 hours to finally obtain the target catalyst (porous Pt@BaTiO3).
[0127] Comparative Example 4
[0128] The conventionally synthesized control catalyst (Pt@BaTiO3) was prepared in the following steps:
[0129] a. Weigh 10 mL of tetrabutyl titanate and add it dropwise into 40 mL of anhydrous ethanol while stirring magnetically to form a uniform titanium source solution; weigh 2.61 g of barium nitrate and dissolve it in 50 mL of deionized water to form a titanium source solution; weigh 3.19 g of Pt(NO3)2 and dissolve it in 500 mL of deionized water, first mix the titanium source solution with the precious metal solution, and then slowly add the mixed solution dropwise into the barium source solution, stirring continuously during the addition, to form a uniform and stable metal salt precursor solution.
[0130] b. Weigh 10 ml of the metal salt precursor solution obtained in step a and age it at room temperature for 12 hours until it turns into a gel state.
[0131] c. Place the gel in step b in an oven and dry it at 100° C. for 12 hours to remove the solvent and moisture in the gel, and finally obtain a dry gel.
[0132] d. Place the dry gel in step c into a muffle furnace, heat it to a predetermined temperature of 1000° C. at a certain heating rate of 10° C. / min, calcine for 3 hours, grind it, and obtain a control catalyst (Pt@BaTiO3).
[0133] Test Example 3
[0134] (I) Effect of conventionally synthesized ferroelectric catalysts loaded with noble metal ions on plasma catalytic removal of toluene
[0135] The experimental process is as follows: 1000ppm toluene is introduced, the total gas flow rate is 1000ml / min, dielectric barrier discharge is used, the input power is within the range of 20W at room temperature and pressure, 0.2g of the conventionally synthesized control catalyst (Pt@BaTiO3) in Comparative Example 4 is taken and placed in situ in the plasma discharge zone to investigate its catalytic effect on toluene in coordination with plasma. As shown in Table 3, the removal rate of toluene is increased by 67.5%, and the energy efficiency is 41.4%.
[0136] (II) Effect of target catalyst loaded with noble metal ions on plasma catalytic removal of toluene
[0137] The experimental process is as follows: 1000ppm toluene is introduced, the total gas flow rate is 1000ml / min, dielectric barrier discharge is used, the input power is within the range of 20W at room temperature and pressure, 0.2g of the target catalyst (porous Pt@BaTiO3) with ferroelectricity synthesized in Example 3 is taken and placed in situ in the plasma discharge zone, and its catalytic effect on toluene in coordination with plasma is investigated. From the results, it can be seen that the target catalyst is used for plasma catalytic removal of toluene up to 97.2%, and the plasma zone energy efficiency is 47.4%, and the removal efficiency is still higher than that of conventional Pt@BaTiO3 catalyst.
[0138] Table 3 Effect of noble metal ion loading and toluene removal in different systems
[0139]
[0140] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for efficiently removing VOCs by plasma in-situ coupling with ferroelectric catalysts, characterized in that: The steps include: Introducing VOCs gas into the plasma region so that the VOCs gas contacts the ferroelectric catalyst placed in the plasma region; The plasma zone is provided by a plasma generator through a dielectric barrier discharge method, and the power supply of the plasma generator is a pulse power supply or an AC power supply; The ferroelectric catalyst comprises a porous metal oxide having ferroelectric properties; The porous metal oxide is a perovskite material with a chemical composition of ABO3, wherein: A is selected from one of Ba, Li, La, Ca and Sr; B is selected from one of Ti, Nb, Fe, Co and Cu.
2. The method according to claim 1, characterized in that The ferroelectric catalyst is prepared by a method comprising the following steps: S1, slowly adding source A solution to source B solution, stirring, to obtain a metal salt precursor solution; Wherein, the A source solution is an aqueous solution of the A metal salt, and the B source solution is an alcohol solution containing the B metal alkoxide; S2, placing the template in a metal salt precursor solution, allowing it to stand for aging to form a gel, and then centrifuging and drying to obtain a template impregnated with the metal salt precursor; S3, heat-treating the template impregnated with the metal salt precursor to remove the template agent to obtain a solid metal oxide phase; The heat treatment is carried out in an oxidizing atmosphere; S4. In an oxidizing atmosphere, calcining the solid metal oxide phase to obtain the ferroelectric catalyst.
3. The method according to claim 2, characterized in that The ferroelectric catalyst further includes a noble metal element supported on the surface of the porous metal oxide; The noble metal is selected from at least one of Au, Pt, Ag, and Pd; In step S1, the B source solution also includes a soluble precious metal salt; In the step S3, the heat treatment is performed in a reducing atmosphere.
4. The method according to claim 2, characterized in that: In step S2, the template is a PMMA template prepared by the Stober-Frink method.
5. The method according to claim 1, characterized in that In step S2, the conditions for static aging include: the aging time is 12 to 48 hours.
6. The method according to claim 1, characterized in that In step S3, the heat treatment conditions include: the heat treatment temperature is 400-800° C., and the heat treatment time is 8-16 hours.
7. The method according to claim 1, characterized in that In step S5, the calcination conditions include: a calcination temperature of 300 to 500° C. and a calcination time of 1 to 9 hours.
8. The method according to claim 7, characterized in that In step S5, the calcination conditions include: heating to 300-350°C and maintaining for 0.5-3h, then heating to 450-500°C and maintaining for 0.5-6h.
9. The method according to claim 1, characterized in that: The working conditions of the pulse power supply are: pulse time is 2 to 10 ns, pulse frequency is 1 to 10 kHz; The working conditions of the AC power supply are: frequency of 50Hz-100kHz, and discharge power of 10-200W.
10. The method according to claim 1, characterized in that The flow rate of VOCs gas is 100~5000mL / min; The concentration of VOCs gas is 20-3000ppm.
Citation Information
Patent Citations
Method for synthesizing perovskite by using natural organic template
CN105753058A
ABO3 type perovskite catalyst, preparation method and application of ABO3 type perovskite catalyst in plasma synergistic catalysis of VOCs
CN111921524A
Porous metal oxide catalyst, preparation method thereof and application of porous metal oxide catalyst in plasma catalytic system
CN115582123A
Microwave auxiliary plasma catalytic air purifier
CN2847126Y
Gas treatment apparatus and gas treatment method
JP2004041862A